EFEKTIVITAS TAYANGAN BELAJAR DARI RUMAH DI TVRI SEBAGAI MEDIA PEMBELAJARAN DALAM MASA DARURAT COVID-19 ( STUDI DI DESA MEKARRAHAYU KAB. BANDUNG) - Annisa Rahma Alimah; Maya Retnasary (Fakultas Dakwah dan Komunikasi, 2020)
Learning shows from home is an educational program broadcast by the Television Station of the Republic of Indonesia (TVRI). This education program is a collaboration between the Ministry of Education and Culture with the National TVRI TVRI with the theme of learning at home during the Covid-19 emergency period. The Learning From Home program is an alternative for students and parents of students who do not have facilities to do distance learning where this distance learning requires internet tools and network facilities. The purpose of this study was to determine the effectiveness of the Learning Show from home at TVRI as a learning medium during the Covid-19 pandemic. This research uses descriptive qualitative research methods by collecting data through observation, interviews, and documentation. The results of this study obtained an overview in the village of Mekar Rahayu in Bandung District on parents of students and elementary school teachers, the results of the study showed that the Learning From Home program on TVRI was quite effective for learning during the Covid-19 emergency period other than helping parents of students who did not have the facilities for the learning of their children also help teachers to recall the children's lessons in the broadcast which had previously been delivered but only a few drawbacks in the category of material delivered.